In-vacuum silicone rubber forming process for soft robots - Yuta Ishikawa; Hiroyuki Nabae; Gen Endo; Koichi Suzumori (ROBOMECH Journal)
Abstract Silicone rubber is widely used in various soft robots, sensors, and actuators. One of the most popular fabrication processes for silicone rubber is molding, which can easily duplicate three-dimensional (3D) shapes using a mold. Among the molding techniques, vacuum molding is a useful approach for preventing defects in molded parts. However, during the vacuum molding process, handling objects in a vacuum is challenging, requiring the mold to be carefully designed to prevent air bubble entrapment without manipulating the silicone rubber pouring point or the mold. In this study, to address these challenges, we propose an in-vacuum silicone rubber forming process. This process allows the silicone rubber pouring point to be controlled in a vacuum using a five-bar parallel link manipulator. This manipulator can be easily installed with only two rotational rods, typically employed as mixing rods within the chamber, facilitating efficient molding processes such as multi-part fabrication with minimal silicone rubber waste without the need for special mold designs. We validate the effectiveness of this process by molding cylindrical structures with diameters ranging from 1.2 to 5 mm and three types of liquid silicone rubbers with viscosities from 3 to 20 $$\text{Pa}· \text{s}$$ Pa · s . Compared to conventional methods—standard molding and vacuum molding, our proposed approach could successfully mold all cylinders without voids or air bubbles. Additionally, the applicability of this method to soft robotics was demonstrated through two applications using major soft actuators, pneumatic actuator and dielectric elastomer actuator (Non-standard abbreviation: DEA—Dielectric Elastomer Actuator), for soft robotics.